Infrastructure Evaluation of TEPRA Information System Application for Development Administration Section of Gianyar Regency - I Made Oka Semara Putra (Doctorate Program of Engineering Science, Faculty of Engineering, Udayana University, 2021)
The development of information technology that has developed in government is very helpful in the process of managing government infrastructure. In the Gianyar Regency Development Section which has implemented a system, namely the TEPRA. TEPRA is a system used to carry out the process of monitoring the realization of the budget given to each OPD (Organisasi Perangkat Daerah) in Gianyar Regency to find out any problems or obstacles that might occur when realizing the program of each related OPD. The frequent mistakes made by TEPRA Operators in completing data information about the program of the relevant OPDs are the reason that it is necessary to carry out an audit of the TEPRA information system. The audit process of the TEPRA information system uses a framework, namely COBIT 4.1. In the research process carried out using COBIT 4.1 and with a total of 110 respondents consisting of the Head of the Bagian Pembangunan, the Head of the Sub-Division of Pengendalian and Pembangunan , TEPRA Staff, and TEPRA Operators in each related OPD, resulting in a maturity level of 3.09 (defined). From the results obtained, generally the TEPRA system has been running or implemented properly. With this maturity level, there is a maturity gap so that improvements need to be made in order to achieve the expected maturity level.